PENGARUH KOMPENSASI, DISIPLIN KERJA DAN PENGEMBANGAN KARIER TERHADAP KINERJA KARYAWAN - Kiffatul Anhar; Taufik Bustami (UM. Bengkulu, 2026)
The research is based on the persistence of differences in employee perceptions of compensation, the suboptimal implementation of work discipline, and the unequal distribution of career development opportunities that impact employee performance. This study aims to analyze the influence of compensation, work discipline, and career development on employee performance at PT. Daria Dharma Pratama Mukomuko, both partially and simultaneously. The research method used is a quantitative method with a survey approach. Data were collected through questionnaires and analyzed using multiple linear regression analysis, validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and coefficients of determination (R²). The results of the study indicate that partially compensation, work discipline, and career development have a positive and significant effect on employee performance. Simultaneously, the three independent variables also have a significant effect on employee performance at PT. Daria Dharma Pratama Mukomuko. This indicates that increasing fair compensation, implementing consistent work discipline, and planned career development can improve employee performance optimally. The conclusion of this study is that compensation, work discipline, and career development are important factors that must be considered by companies in an effort to improve employee performance. Therefore, companies are advised to continue to improve the compensation system, improve work discipline, and provide equal career development opportunities to support the achievement of company goals. Keywords: Compensation, Work Discipline, Career Development and Employee Performance